Intestinal histopathology and immune responses following Escherichia coli lipopolysaccharide challenge in Nile tilapia fed enriched black soldier fly larval (BSF) meal supplemented with chitinase. - LALEYE, PHILIPPE A. (My University, 2022)
This study aimed to determine to what extend the addition of chitinase to black soldier fly larvae (BSF) meals enriched with either PUFA or LC-PUFA could improve the gut health of Nile tilapia and increase its immune status. Two types of BSF meals enriched with either α-linolenic acid (ALA) or ALA + eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) were produced using BSF larvae cultured on vegetable substrates (VGS) or fish offal substrates (FOS), respectively. Seven diets were formulated: a control FMFO diet and two other control diets VGD0 vs FOD0 containing the meals of each type of BSF meal as total replacement for fishmeal (FM) and fish oil (FO), as well as four diets supplemented with chitinase. Two doses of commercial chitinase from Aspergillus niger (2 g/kg and 5 g/kg of feed) were supplemented to the other diets VGD0 and FOD0 to formulate VGD2, VGD5, FOD2 and FOD5. After 53 days of feeding, FOD5 diet induced a similar growth performance as the FMFO control diet, while a significant decrease of growth was observed for the other BSF larval-based diets. BSF/FOS meal led to higher SGR of fish than BSF/VGS, as for the FOD5 compared to VGD5. At day 53, lysozyme values showed an increasing trend in fish fed all the BSF-based diets, especially those fed the VGD5. After the Escherichia coli lipopolysaccharide (LPS) injection (day 54), the same increasing trend was observed in lysozyme activity, and modulation was observed only in the VGD5 fish. ACH50 activity was reduced by the BSF-based diets except for the FOD5 diet at day 53, and LPS modulation was only observed for the VGS-chitinase-based diets at day 54. Peroxidase activity and total immunoglobulin (Igs) blood level were not affected by substrate, chitinase dose or LPS injection. At day 53, the low or high dose of chitinase increased the expressions of tlr2, il-1β and il-6 genes in the head kidney of fish fed the BSF/VGS diets compared to those fed the VGD0 or FMFO control diets. At day 54 after LPS injection, the high dose of chitinase decreased the expressions of tlr5 gene in the spleen and mhcII-α gene in the head kidney of fish fed FOD5 diets compared to those fed FOD0 diets. BSF/VGS but not BSF/FOS based diets increased fish sub-epithelial mucosa (SM) and lamina propria (LP) thickness and the number of goblet cells (GC) in fish, but dietary chitinase seemed to prevent some of these effects, especially at low dose. Results showed that chitinase supplementation of 5 g/kg of chitinase to a BSF-based diet enriched with LC-PUFA improved growth, prevented histological changes in the proximal intestine and enhanced some innate immune functions of Nile tilapia without any clear booster effect after challenge with E. coli LPS.
Keywords: Chitinase; Growth; Hermetia illucens; Immune modulation; Oreochromis niloticus.